Hunting and Forest Modification Have Distinct Defaunation Impacts on Tropical Mammals and Birds - Osuri, Anand M.; Mendiratta, Uttara; Naniwadekar, Rohit; Varma, Varun; Naeem, Shahid (Frontiers in Forests and Global Change, 2020)
The mammalian and avian assemblages of intact tropical forests are among the most diverse vertebrate communities on Earth and influence the structure, composition and functioning of these forests in myriad ways. Over recent centuries, however, increasing human domination of the tropics has led to widespread defaunation, or the decline, local- or global extinction of tropical animal species. Defaunation is one of the defining features of the Anthropocene and is best documented for vertebrate species, especially mammals and birds. Defaunation is driven by several direct (e.g., hunting) and indirect (e.g., habitat alteration) anthropogenic threats, but how these threats differ in the nature and magnitude of their impacts on tropical mammal and bird species remains unclear. Using a meta-analysis of 82 studies on 254 mammal and 1640 bird species from across the tropics, we assess the effects of three major regional-scale drivers of tropical defaunation, namely hunting, forest degradation and forest conversion, on measures of abundance for tropical mammal and bird species belonging to different dietary guilds and IUCN conservation status groups. Mammal species across dietary guilds declined or did not vary, on average, in response to the three drivers, with hunting having the most consistent negative impacts on abundances of carnivores, frugivores, herbivores/granivores, large-bodied species, and species of high conservation importance. By contrast, bird species declined most strongly in response to forest conversion, with responses varying widely across different dietary and conservation importance groups, and not consistently related to body size. Our results reveal that hunting, forest degradation and conversion are associated with distinct types of defaunation of mammal and bird species, and are therefore likely to have distinct implications for animal-mediated interactions and processes, ecosystem functions, and conservation of tropical forests. Addressing major gaps in our empirical understanding of defaunation effects – e.g., hunting impacts on smaller-bodied mammals and birds, and responses of species in southeast Asian forests – is key to better understanding, predicting, and mitigating the impacts of this pervasive global threat.